Aplikasi Delivery Order Makanan Dan Minuman Berbasis Web Pada Restoran Mang Kabayan - Syifa Nur Rakhmah; Reza Reza; Kardinal Novel (Jurnal Teknika, 2019)
The utilization of smartphone technology in various aspects has now been felt, without exception reaching restaurants that want to use technology for the satisfaction of customers and the benefits of restaurants. Humans in general want everything to be easily done, as well as restaurant customers who want to order menus easily in the sense that it is not complicated and does not take a long time. It's easy to order the menu in question without having to queue and without waiting for the waiter to be busy with other customers. Restaurant customers can also take time to order orders according to their needs so they are not disturbed by the presence of a waiter who is waiting for the order. The preparation of this study uses two research methods, namely, data collection methods and software development methods, namely using the waterfall method. To overcome the problems that the authors describe, a web-based application is made to make it easier for restaurants and customers to order food. With the use of media websites that have been published can facilitate food ordering in real time.